The impact of characteristic factors of the direct-to-consumer marketing model on consumer loyalty in the digital intermediary era - Mu, Weizhe; Yi, Yating (Frontiers in Psychology, 2024)
In the era of digital intermediaries, the direct-to-consumer (DTC) marketing model is gaining prominence in the retail and brand marketing domains. This model exhibits a distinct advantage over traditional models in cultivating loyalty. Consequently, this study employs a survey-based approach and utilizes the Stimulus-Organism-Response (SOR) theory to construct a structural equation model and investigate the relationship between the DTC marketing model's characteristic factors and consumer loyalty. The results indicate that cost-effectiveness and social media marketing directly and positively influence consumer loyalty, while product features indirectly contribute to loyalty through perceived emotional value. Multi-channel integration indirectly influences loyalty through perceived functional value. Additionally, the varying degrees of influence highlight social media marketing as the most impactful factor and product features as the least influential. The research findings underscore the importance of strengthening social media marketing, optimizing product features, reducing information asymmetry, and integrating multiple channels to enhance consumer loyalty. This study enriches the understanding of the DTC theoretical framework in the field of marketing and provides new perspectives for formulating marketing strategies.